Extra-linguistic Factors Affecting Learner's English Speaking at the Tertiary Level in Bangladesh (IUBAT Review, 2023)
This study investigates the primary speaking difficulties encountered by tertiary-level English as Foreign Language (EFL) learners in Bangladesh and explores the influence of extra-linguistic factors on their English-speaking abilities. The research involves 77 participants from six Bangladeshi universities who have completed at least one English-speaking course. Utilizing a Likert-scale questionnaire encompassing 13 closed-ended questions, the study employs a quantitative approach. The findings reveal that speaking challenges are prevalent among EFL learners, with major difficulties including lack of conceptual knowledge, fluency, vocabulary, confidence, and grammar. Additionally, cultural, psychological, educational, and social factors significantly influence speaking proficiency. The cultural influences encompass pronunciation, communication styles, and idiom comprehension—where psychological factors like confidence and fear of making mistakes play a vital role. Educational factors, including classroom environments and feedback mechanisms, play a vital role. Engagement with English media and real-life English interactions also affect speaking skills. The study suggests cultural sensitivity, psychological support, improved learning environments, feedback mechanisms, media engagement, and increased real-world contacts to boost speaking proficiency in EFL learners.IUBAT Review, 6(2): 92-105